Poesia premiada : a produção contemporânea para crianças e jovens no Brasil (2000-2009) - Furtado, João Carlos Dias (2011)
Is a study that aims to analyze contemporary youth and children's poetry and to score the important features of publishing, graphic design and awards involving production and marketing. Therefore, this work presents a theoretical review of the concepts of literature (poetry and narrative poetry) and the story focused on childhood and youth, in order to accomplish the analysis of the works contemplated by Jabuti Award (Brazilian Book Chamber) and by the prize of National Children and Youth Book Foundation (FNLIJ) in the period from 2000 to 2009. From the theoretical framework that includes poetry and nursery rhymes and youth, the analysis addresses the aspects of graphic design and thematic and formal structure of the books of poems, to discuss key points of this production: the language, adapting the project to public, the theme and the influence of market and production awards. The analysis finds a creative and charming landscape; the award-winning books feature rich graphics projects which explore the redefinition of the poetic text with colors, images and textures. The themes are basically concentrated in the daily universe of children and adolescents, with their problems, dreams and games; the formal structure of the poems indicates a freedom that does not hold the classical forms, and when that happens, the goal is to catch the eye of the reader to a moment, a situation or a specific context; the sonority, rhythm, and figures of speech have open and fluid passage through the poems and titles discussed.